Coordinated distributed experiments: an emerging tool for testing global hypotheses in ecology and environmental science. Issue 3 (14th December 2012) - Fraser, Lauchlan H; Henry, Hugh AL; Carlyle, Cameron N; White, Shannon R; Beierkuhnlein, Carl; Cahill, James F; Casper, Brenda B; Cleland, Elsa; Collins, Scott L; Dukes, Jeffrey S; Knapp, Alan K; Lind, Eric; et al.
Abstract : There is a growing realization among scientists and policy makers that an increased understanding of today's environmental issues requires international collaboration and data synthesis. Meta‐analyses have served this role in ecology for more than a decade, but the different experimental methodologies researchers use can limit the strength of the meta‐analytic approach. Considering the global nature of many environmental issues, a new collaborative approach, which we call coordinated distributed experiments (CDEs), is needed that will control for both spatial and temporal scale, and that encompasses large geographic ranges. Ecological CDEs, involving standardized, controlled protocols, have the potential to advance our understanding of general principles in ecology and environmental science.